Asymmetric Preorganization of Inverted Pair Residues in the Sodium-Calcium Exchanger - Giladi, Moshe (Sci Rep, 2016)
In analogy with many other proteins, Na(+)/Ca(2+) exchangers (NCX) adapt an inverted twofold symmetry of repeated structural elements, while exhibiting a functional asymmetry by stabilizing an outward-facing conformation. Here, structure-based mutant analyses of the Methanococcus jannaschii Na(+)/Ca(2+) exchanger (NCX_Mj) were performed in conjunction with HDX-MS (hydrogen/deuterium exchange mass spectrometry) to identify the structure-dynamic determinants of functional asymmetry. HDX-MS identified hallmark differences in backbone dynamics at ion-coordinating residues of apo-NCX_Mj, whereas Na(+)or Ca(2+) binding to the respective sites induced relatively small, but specific, changes in backbone dynamics. Mutant analysis identified ion-coordinating residues affecting the catalytic capacity (k(cat)/K(m)), but not the stability of the outward-facing conformation. In contrast, distinct “noncatalytic” residues (adjacent to the ion-coordinating residues) control the stability of the outward-facing conformation, but not the catalytic capacity. The helix-breaking signature sequences (GTSLPE) on the α(1) and α(2) repeats (at the ion-binding core) differ in their folding/unfolding dynamics, while providing asymmetric contributions to transport activities. The present data strongly support the idea that asymmetric preorganization of the ligand-free ion-pocket predefines catalytic reorganization of ion-bound residues, where secondary interactions with adjacent residues couple the alternating access. These findings provide a structure-dynamic basis for ion-coupled alternating access in NCX and similar proteins.